2013
DOI: 10.1177/197140091302600502
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging of Neural Tissue Organization: Correlations between Radiologic and Histologic Parameters

Abstract: Summary Objective This study examined the relationship between histological variables and DTI values in a normal canine brain. We hypothesized that radial diffusivity (RD) would correlate with myelin density and fractional anisotropy (FA) would correlate with white matter fiber coherence Specimens and methods We acquired DTI maps of a normal canine brain post mortem on a 7T MR scanner (TR = 100 ms, TE = 18.1 ms, NEX = 1, width [d] = 4 ms, separation [D] = 8.9 ms, gradient amplitude = 600 mT/m, b=1,565 s/mm2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Alterations in astrocyte morphometry and function are associated with suicide (Ernst et al, 2011, Torres-Platas et al, 2011). Additionally, as RD is thought to be a marker of myelination (Song et al, 2002, Wei et al, 2013), our findings may reflect oligodendrocyte dysfunction and myelination deficits, which are themselves associated with suicide (Klempan et al, 2009a, Klempan et al, 2009b). The gray matter findings were more focal and limited.…”
Section: Discussionmentioning
confidence: 87%
“…Alterations in astrocyte morphometry and function are associated with suicide (Ernst et al, 2011, Torres-Platas et al, 2011). Additionally, as RD is thought to be a marker of myelination (Song et al, 2002, Wei et al, 2013), our findings may reflect oligodendrocyte dysfunction and myelination deficits, which are themselves associated with suicide (Klempan et al, 2009a, Klempan et al, 2009b). The gray matter findings were more focal and limited.…”
Section: Discussionmentioning
confidence: 87%
“…A number of studies have used DTI to follow serial changes in the brain after therapy (McGraw et al, 2005). However, few studies have validated DTI metrics by providing histological correlates of the major DTI parameters, such as FA and radial diffusivity (Song et al, 2002; Wei et al, 2013). One investigator has previously shown that radial diffusivity, but not FA, correlated with degree of demyelination based on Luxol fast blue-stained slides of spinal cord derived from multiple sclerosis patients (Klawiter et al, 2011), However, unlike our study, that investigation was based on a semi-quantitative grading system for degree of demyelination (rather than on a quantitative analysis of myelin content) and also did not measure response to a treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional anisotropy has been demonstrated to reflect features that constrain water diffusion in white matter, including myelination and other microstructural factors (201). With optimization of these parameters, DTI may become a more useful tool in diagnosing strokes in dogs (200)(201)(202).…”
Section: Tractography Diffusion Tensor Imaging (Dti) (Figure 11)mentioning
confidence: 99%